FINISHING KAYU KELAPA (Cocos nucifera, L) UNTUK BAHAN INTERIOR RUANGAN - Purwanto, Djoko (Kementerian Perindustrian, 2011)
Finishing of coconut wood use the polyurethane, melamine formaldehyde and ultran vernis with the spraying 1 times and 2 times. Research target for the change of performance of colour and fibre of coconut wood more interesting. Result of research indicate that the use of substance of finishing polyurethane, melamine formaldehyde and ultran vernis can change the colour and fibre. Before coconut wood doneÂ finishing have the black chocolate colourÂ andÂ fibre pattern rather dark. After doing finishing colour become the squeezing chocolate, fibre pattern rather look and flatten.Keywords: coconut wood, finishing, interior materi, bahan interior, polyurethane, melamine formaldehide, ultran vernis.